Zbol and Sorvebol: from networks to school (Research, Society and Development, 2023)
The study aimed to analyze the teachers' perceptions about Sorvebol and Zbol. An investigation was carried out with 10 teachers from five municipal public schools in Macapá-AP. A questionnaire with open questions was applied. In the results it was evidenced that these sports still suffer difficulties of acceptance by the students in detriment of the hegemonic presence of others already known. They are still little known to students. These sports are confused with game content. These sports are able to meet the needs of spaces and materials, making it possible to perform them in different spaces, with adapted and easy-to-manufacture materials. The continuity of research with these sports is important for the knowledge of the scientific, school and general community.